The interaction of phospholipase A2 with a phospholipid bilayer: coarse-grained molecular dynamics simulations. - Wee, C; Balali-Mood, K; Gavaghan, D; Sansom, MS (2008)
A number of membrane-active enzymes act in a complex environment formed by the interface between a lipid bilayer and bulk water. Although x-ray diffraction studies yield structures of isolated enzyme molecules, a detailed characterization of their interactions with the interface requires a measure of how deeply such a membrane-associated protein penetrates into a lipid bilayer. Here, we apply coarse-grained (CG) molecular dynamics (MD) simulations to probe the interaction of porcine pancreatic phospholipase A2 (PLA2) with a lipid bilayer containing palmitoyl-oleoyl-phosphatidyl choline and palmitoyl-oleoyl-phosphatidyl glycerol molecules. We also used a configuration from a CG-MD trajectory to initiate two atomistic (AT) MD simulations. The results of the CG and AT simulations are evaluated by comparison with available experimental data. The membrane-binding surface of PLA2 consists of a patch of hydrophobic residues surrounded by polar and basic residues. We show this proposed footprint interacts preferentially with the anionic headgroups of the palmitoyl-oleoyl-phosphatidyl glycerol molecules. Thus, both electrostatic and hydrophobic interactions determine the location of PLA2 relative to the bilayer. From a general perspective, this study demonstrates that CG-MD simulations may be used to reveal the orientation and location of a membrane-surface-bound protein relative to a lipid bilayer, which may subsequently be refined by AT-MD simulations to probe more detailed interactions.